Management of public hospitals by Social Health Organisations in Piauí - BARROS, ADRIANA; Pereira, Sofia Laurentino Barbosa (Argumentum, 2026)
The Brazilian Unified Health System (SUS) resulted from of a process of disputes, in which the role of Health Reform played an important role, and which was linked to a democratic and emancipatory societal project. This is in contrast to the neoliberal project of capital which transforms health into a commodity. Employing a qualitative narrative literature review, this article analyses the management of public health facilities, especially that of hospitals, by Social Health Organisations (OSS) in Brazil generally, and specifically in the State of Piauí, as an expression of a process of privatisation of the SUS and sequestration of public funds. In the case of Piauí, management by OSS, carried out without broad debate within civil society, challenges the public, free, universal, and participatory character of the SUS, reinforcing the consolidation of a privatised health model that serves the interests of capital.
Keywords: Health; Privatisation; Social Health Organisations; Piauí (State)